From Book To Bookish: Repurposing the Book in the Digital Era - Nicola Rodger (communication +1, 2018)
Attacked. Defended. Worshipped. Ridiculed. Recycled. Books today are subject to all of these treatments. Books are used as home décor, mousepads, bill folders, and sculptures. Books are also pulped and anonymously converted into other, non-book related products. It is no coincidence that such transformations and transmutations abound, nor that these bookish forms are variously being shared, promoted or decried. The current digital era both encourages and enables this. But why is the book object still celebrated? How do these celebrations of the book manifest? How much of the ongoing cultural interest in the book is driven by its materiality? Focusing on just one way in which these celebrations manifest, this article displaces questions of text and authorship and instead offers a refreshed, object-orientated account of books today as lively, material ‘things’ and interrogates our taken-for-granted relationships with them. As evidenced in physical and virtual spaces, there is ongoing interest in the book object, bookish objects, book spaces and fascination with the hold that these objects and spaces have on people. Drawing together visual evidence (that resides on my publicly-accessible Pinterest boards), I demonstrate the broader levels of cultural obsession that surround the book object, an obsession that is becoming ever clearer in today’s digital era. This rich examination of the book object draws upon a range of theoretical approaches which can be gathered together under the umbrella of new materialism. Featured theoretical frameworks include: vital materialism and enchantment (Bennett 2010; 2001), thing theory (Brown 2003), sacredness and ritualization (Alasuutari 2006; Bell 1992) ecocriticism and the ethics of waste (Dryzek 2013; Fox 2000; Hawkins 2006; Scanlan 2005); embodied experience as a site of knowledge (Alaimo 2010; Merleau-Ponty 2012; Littau 2006); liquid modernity (Bauman 2000) and Actor-Network-Theory (Akrich and Latour 1994; Latour 2005). With this article I present a framework through which to consider how important embodiment is to the concept of the book and the status of the book today. Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: Book; book art; new materialism; vibrant matter